Język dyskursu publicznego w polskim systemie politycznym - Balczyńska-Kosman, Alina (Środkowoeuropejskie Studia Polityczne i Medioznawcze, 2013)
These days, political actors use the language of politics not only as a means of communication but as an instrument of competition. Politics is becoming an area of social activity which to a large extent is constituted by words. The issues discussed in this paper involve the definitions of basic concepts and an indication of participants in public discourse, a determination of discourse content and the styles of language of politics, and the conclusions of the study. The paper emphasizes that the contemporary language of public discourse in the Polish political system is highly colloquial, negative and very often characterized by a lack of respect for opponents. Its participants include political actors, mass media, and the recipients of messages. The language of discourse is primarily shaped by the media in the process of message priming, framing and tabloidization.